2022
DOI: 10.3390/diagnostics12030648
|View full text |Cite
|
Sign up to set email alerts
|

First Characterization of ADAMTS-4 in Kidney Tissue and Plasma of Patients with Chronic Kidney Disease—A Potential Novel Diagnostic Indicator

Abstract: Background: We have previously shown that metzincin protease ADAMTS-4 accompanies renal fibrogenesis, as it appears in the blood of hemodialysis patients. Methods: Native kidney (NKB) and kidney transplant (TXCI) biopsy samples as well as plasma from patients with various stages of CKD were compared to controls. In paired analysis, 15 TXCI samples were compared with their zero-time biopsies (TX0). Tissues were evaluated and scored (interstitial fibrosis and tubular atrophy (IFTA) for NKB and Banff ci for TXCI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…[ 21 ] A comparison of ADAMTS4 expression in the native and transplanted kidney biopsy specimens and plasma of CKD patients at different stages showed that ADAMTS4 as associated with RF in hemodialysis patients. [ 22 ] These findings suggest that members of the ADAMTS family are involved in the progression of kidney injury. The ADAMTS18 gene is one of the hidden genes that has just begun to be studied in the field of epigenetics.…”
Section: Discussionmentioning
confidence: 99%
“…[ 21 ] A comparison of ADAMTS4 expression in the native and transplanted kidney biopsy specimens and plasma of CKD patients at different stages showed that ADAMTS4 as associated with RF in hemodialysis patients. [ 22 ] These findings suggest that members of the ADAMTS family are involved in the progression of kidney injury. The ADAMTS18 gene is one of the hidden genes that has just begun to be studied in the field of epigenetics.…”
Section: Discussionmentioning
confidence: 99%
“…CKD is a heterogeneous disease that may occur due to multiple underlying disorders and is defined by the KDIGO initiative as “abnormalities of kidney structure and/or function, present for over three months, with implications for health” [ 63 , 64 , 65 ]. Causes of the disease can vary from genetic heritability to diabetes, hypertension, and glomerulonephritis as well as heart disease, obesity, and old age [ 66 , 67 ].…”
Section: Nag In Kidney Injurymentioning
confidence: 99%
“…Other major substrates of ADAMTS-4 are proteoglycans expressed physiologically in smooth muscle cells of blood vessels like versican and aggrecan, principal vessel wall proteoglycans that are targeted by ADAMTS-4, driving blood vessel atrophy. 17,20 Considering all of the above, we conducted a small pilot crosssectional observational study in order to determine possible differences between ADAMTS-4 concentrations in patients with HA and OA, obtaining plasma from patients with both diseases in severe and mild stage. To the best of our knowledge, there are no published studies showing differences in ADAMTS-4 blood/plasma concentration between OA and HA patients.…”
Section: Introductionmentioning
confidence: 99%
“…One of its main targets is the proteoglycan aggrecan, a major structural and functional proteoglycan of the articular cartilage. Other major substrates of ADAMTS‐4 are proteoglycans expressed physiologically in smooth muscle cells of blood vessels like versican and aggrecan, principal vessel wall proteoglycans that are targeted by ADAMTS‐4, driving blood vessel atrophy 17,20 …”
Section: Introductionmentioning
confidence: 99%